2013
DOI: 10.11604/pamj.2013.14.8.1050
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinome de l'ouraque: une cause rare d'hematurie

Abstract: Les cancers de l'ouraque sont rares et de pronostic sombre. Les auteurs rapportent un cas d'adénocarcinome de l'ouraque révélé par une hématurie et exploré par échographie et tomodensitométrie abdominopelvienne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Abdominal obesity was defined by a WC ≥ 94 cm for both men and women. WC ≥ 94 cm provided the same rate of abdominal obesity as reported in our previous study [18] and in other studies [19, 20]. MS has been defined as the presence of three or more of the following five risk factors: 1) abdominal obesity (WC ≥ 95 cm in men and in women); 2) hypertriglyceridemia (triglycerides (TG) ≥ 150 mg/dL or use of medications to lower triglycerides); 3) decreased high-density lipoprotein cholesterol HDL-C (<40 mg/dL in men and <50 mg/dL in women or use of medication to increase HDL-C); 4) high blood pressure (systolic blood pressure ≥130 mmHg and/or diastolic blood pressure ≥85 mmHg and/or use of antihypertensive medication); 5) high fasting plasma glucose ≥100 mg/dL or use of hypoglycemic medication.…”
Section: Methodssupporting
confidence: 75%
“…Abdominal obesity was defined by a WC ≥ 94 cm for both men and women. WC ≥ 94 cm provided the same rate of abdominal obesity as reported in our previous study [18] and in other studies [19, 20]. MS has been defined as the presence of three or more of the following five risk factors: 1) abdominal obesity (WC ≥ 95 cm in men and in women); 2) hypertriglyceridemia (triglycerides (TG) ≥ 150 mg/dL or use of medications to lower triglycerides); 3) decreased high-density lipoprotein cholesterol HDL-C (<40 mg/dL in men and <50 mg/dL in women or use of medication to increase HDL-C); 4) high blood pressure (systolic blood pressure ≥130 mmHg and/or diastolic blood pressure ≥85 mmHg and/or use of antihypertensive medication); 5) high fasting plasma glucose ≥100 mg/dL or use of hypoglycemic medication.…”
Section: Methodssupporting
confidence: 75%
“…The current study did not indicate any significant association between malaria infection and anemia while other studies [29, 40, 41] reported significant association between malaria infection and anemia. This might not be an indicator that malaria infection did not have an effect on anemia; rather the variation might be attributed to relatively lower malaria prevalence compared to studies in Kisumu, Western Kenya [40], and Enugu, Southeast Nigeria [42]. Application of community-based study design in Gilgel Gibe Dam area [29] and Sidama Zone, Southern Ethiopia [41], might be another reason for the difference.…”
Section: Discussionmentioning
confidence: 99%